Acute ischemic stroke in adolescents. (14th January 2020) - Rambaud, Thomas; Legris, Nicolas; Bejot, Yannick; Bellesme, Céline; Lapergue, Bertrand; Jouvent, Eric; Pico, Fernando; Smadja, Didier; Zuber, Mathieu; Crozier, Sophie; Lamy, Catherine; Spelle, Laurent; et al.
Abstract : Objective: Adolescence represents a transition period between childhood and adulthood, and only limited information exists about stroke characteristics in this population. Our aim was to describe the clinical and neuroradiologic features, etiologies, initial management, and outcome of ischemic stroke in adolescents. Methods: This retrospective cohort study evaluated all consecutive patients 10 to 18 years with a first-ever ischemic stroke hospitalized between 2007 and 2017 in 10 French academic centers representing a population of ≈10 million. Extracted data from the national database served as validation. Results: A total of 60 patients were included (53% male, median age 15.2 years). Diagnosis at first medical contact was misevaluated in 36%, more frequently in posterior than anterior circulation strokes (55% vs 20% respectively, odds ratio 4.8, 95% confidence interval 1.41–16.40, p = 0.01). Recanalization treatment rate was high (n = 19, 32%): IV thrombolysis (17%), endovascular therapy (11.7%), or both IV and intra-arterial thrombolysis (3.3%); safety was good (only 1 asymptomatic hemorrhagic transformation). Despite thorough etiologic workup, 50% of strokes remained cryptogenic. The most common determined etiologies were cardioembolism (15%), vasculitis and autoimmune disorders (12%, occurring exclusively in female patients), and arterial dissections (10%, exclusively in male patients). Recurrent ischemic cerebrovascular events occurred in 12% (median follow-up 19 months). Recurrence rate was 50% in patients with identified vasculopathy but 0% after cryptogenic stroke. Functional outcome was favorable (Rankin Scale score 0–2 at day 90) in 80% of cases. Conclusions: Ischemic strokes in adolescents harbor both pediatric and adult features, emphasizing the need for multidisciplinary collaboration in their management. Recanalization treatments appear feasible and safe.